Application of the Cooperative Health Care Clinic Model for Delivery of Complementary/Alternative Medicine (CAM) Care - Elder, Charles (Perm J, 2003)
CONTEXT: Patient demand, physician practice patterns, and legislative pressures collectively mandate continuing attention toward determining the most sensible means of providing complementary/alternative medicine (CAM) services and integrating such care within the conventional delivery system at Kaiser Permanente (KP). OBJECTIVE: To assess feasibility of implementing—and customer satisfaction with—an internal, physician-directed, referral-based natural medicine clinic at KP based on the cooperative health care clinic (CHCC) model. DESIGN: Cross-sectional survey. MAIN OUTCOME MEASURES: Responses to a set of three questionnaires administered to patients and to referring clinicians for clinic visits occurring between February 1, 2001 and September 30, 2001. RESULTS: Since inception of the natural medicine clinic in July 1999, the volume of referrals to the clinic has progressively increased, doubling from approximately nine per month during the first eight months of operation to 18 per month during the pilot study. Fifty-six new patients completed the survey instrument by the conclusion of the study; 88% of these 56 patients were either somewhat or highly satisfied with their clinic visit. Of 38 patients seen for follow-up visits, 21 returned a second questionnaire by mail; 88% of these 21 patients reported finding the clinic somewhat or very useful and described improvement in disease-specific symptoms and energy level as well as an enhanced sense of control over their medical condition. Referring physicians reported that the clinic filled a valuable need for them as well as for their patients. CONCLUSION: The CHCC model may be a viable mechanism for delivering CAM services at KP.